Prevalence of work-related musculoskeletal symptoms among young orthopedics during the surgical practice: an intervention study - Cacciatori, Barbara; Schiattarella, Raffaele; Larese Filon, Francesca (La Medicina del Lavoro, 2022)
Background: Work-related muscle-skeletal symptoms (WRMS) represent a substantial social and economic impact on the way of work and have a high incidence in surgeons. In the literature, several studies address the impact of WRMS in surgeons performing gynecological, laparoscopic, and robotic surgery, but there are no studies in the field of orthopedic surgery. This pilot study aims to assess the effectiveness of a preventive program to reduce pain. Methods: All workers filled in a standardized questionnaire, and postoperative pain in the operating room was quantified using a numeric scale (NAS). The intervention group followed ergonomic principles in the operating room supervised by a physiotherapist and specific physical exercises before and after surgery. Data were analyzed using the statistical program STATA rel. 14.0. Results: Twenty-one surgeons were assigned to intervention groups and thirty-three to controls. At baseline, the two groups were homogeneous for anthropometric factors, and controls were older and with higher work seniority. Pain perception resulted in high in both groups in many body districts. At follow-up, after three months, the intervention group significantly reduced pain perception in all body districts for the lumbar back, knees, ankles and feet (p<0.05). In the control group, pain perception increased in all body districts investigated. Conclusions: We found a high prevalence of WRMS in young orthopedic surgeons, and we demonstrated the effectiveness of a preventive program through targeted ergonomic education and exercises for the most affected body districts.